GaSb asosidagi tunnel diodlari volt–amper xarakteristikasining deformatsiya ta‘sirida o‗zgarishi (SCIENCE and SOCIETY, 2025)
This paper presents a theoretical study of the effect of mechanical deformation on the current-voltage characteristics (I-V) of GaSb-based tunnel diodes. Based on the Esaki model, deformation effects were incorporated into the tunneling current expression through the reduced effective mass. The modeling results show that, in the absence of deformation, the I-V characteristics agree well with classical theory and available experimental data. The distinct influence of compressive and tensile strain was identified, demonstrating that the parameters of tunnel diodes can be controlled by